2022
DOI: 10.1007/s00268-022-06742-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Liver Failure in Non‐Cirrhotic Patients Undergoing Hepatectomy

Abstract: Background Post‐hepatectomy liver failure (PHLF) is associated with high mortality following liver resection. There have been limited studies evaluating predictors of PHLF and clinically significant PHLF in non‐cirrhotic patients. Methods This was a retrospective cohort study using the National Surgical Quality Improvement Program database (NSQIP) to evaluate 8,093 non‐cirrhotic patients undergoing hepatectomy from 2014 to 2018. Primary endpoints were PHLF and clinically significant PHLF (PHLF grade B or C). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
0
1
Order By: Relevance
“… 25 , 26 A cohort study that aimed to investigate risk factors for post‐hepatectomy liver failure showed that 4.09% (171/4178) of patients with liver metastases developed liver failure after hepatectomy. 27 However, in our study, only 0.76% (5/654) of patients with hepatic failure developed liver metastases.…”
Section: Discussioncontrasting
confidence: 65%
“… 25 , 26 A cohort study that aimed to investigate risk factors for post‐hepatectomy liver failure showed that 4.09% (171/4178) of patients with liver metastases developed liver failure after hepatectomy. 27 However, in our study, only 0.76% (5/654) of patients with hepatic failure developed liver metastases.…”
Section: Discussioncontrasting
confidence: 65%